Induction in Pancreas Transplantation: T-cell Depletion Versus IL-2 Receptor Blockade - Fahad Aziz, MD; Sandesh Parajuli, MD; Dixon Kaufman, MD; Jon Odorico, MD; Didier Mandelbrot, MD (Transplantation Direct, 2022)
Background. There is limited data exist on relative outcomes with T-depletion versus IL-2 receptor (IL2R) blockade induction in pancreas transplantation. Methods. We analyzed all patients who underwent simultaneous pancreas-kidney or pancreas transplant alone at our institution between January 1, 2011, and December 31, 2019. Results. Of 417 pancreas transplant recipients, 291 received induction with a T-depleting agent and 126 received induction with an IL2R blocker. No difference was detected in pancreas allograft death-censored (P = 0.7) or uncensored (P = 0.5) survival. Although pancreas rejection was more common overall (P = 0.03), this difference was no longer present in recipients at low immunologic risk (P = 0.08). Cytomegalovirus and bacterial infections were significantly more common in the patients who received T-cell depleting agents for induction (21% versus 11%, P = 0.03; 34% versus 23%, P = 0.04, respectively). On multivariate analysis, history of pancreas rejection (Hazard ratio (HR) = 4.7, P = 0.0001; 95% Confidence interval (CI), 2.16-10.12) and higher calculated panel reactive antibodies (HR = 1.01, P = 0.04; 95% CI, 1.0002-1.02) were associated with increased risk of pancreas allograft failure, but choice of induction was not (HR = 0.64, P = 0.3; 95% CI, 0.27-1.51). Further, on multivariate analysis, Cytomegalovirus infection was associated with increased risk of pancreas allograft rejection (HR = 1.78, P = 0.01; 95% CI, 1.11-2.87), but choice of induction was not (HR = 0.84, P = 0.46; 95% CI, 0.54-1.32). Similarly, bacterial infection was associated with increased risk of patient death (HR = 2.94, P = 0.04; 95% CI, 1.03-8.32). Conclusion. Our data suggest that IL-2 receptor blockade may be a reasonable choice of induction for pancreas transplant recipients at low immunologic risk.